SITUATIONAL AND SPIRITUAL LEADERSHIP IN AN ISLAMIC PERSPECTIVE - Abdul Hamid (PT. Jurnal Center Indonesia Publisher, 2025)
Leadership in Islam is a mandate that demands responsibility, justice, and spiritual values. This research aims to explain the integration between situational and spiritual leadership in an Islamic perspective. The method used is a literature study by examining various scientific sources related to the concept of leadership. The results of the study show that situational leadership emphasizes the ability of leaders to adapt to the conditions of followers, while spiritual leadership is based on divine values, trust, and sincerity. Both, when integrated, give birth to a leadership model that is adaptive, moral, and oriented towards the benefit of the ummah as exemplified by the Prophet Saw.